Improving Students’ Achievement in Speaking Monologue Text by Using Video - Masitowarni Siregar; Ratna Eswarny (Budapest International Research and Critics University, 2020)
This study aimed at increasing grade VII students’ achievement in speaking monologue text by using media for English in SMP Negeri 29 Medan, Indonesia. Video as learning media needs to be used to increase students' speaking skills. The method of research used was Classroom Action Research (CAR). The research procedure included planning, implementation of actions, observation and reflection. The techniques used in this study were questionnaires, interviews, and observations. The data were analyzed by quantitative and qualitative techniques. Based on the results of the research and discussion, it can be concluded that the use of media could improve the quality of results and the learning process of English speaking aspects which increased the average students’ score in the initial data was 57.7% to 58.31% (cycle I) and increased to 65.78% (cycle II), the average score of classical completeness also increased from the original 15.6% (initial data) to 37.5% (cycle II) and 81.25% (cycle II). Then, fluency was the highest increasing in improving the students’ speaking ability which was 0,29 from cycle I to cycle II